2007
DOI: 10.1103/physreve.75.012201
|View full text |Cite
|
Sign up to set email alerts
|

Shear waves and shocks in soft solids

Abstract: We study the motion of a sphere falling through soft viscoelastic materials when the time scale of the motion is short compared to the elastic relaxation time of the material. We observe shocks generated by the passage of the sphere at Mach numbers greater than 1. The sphere can undergo oscillations before reaching a steady terminal speed, and we show that these oscillations have the same frequency as the shear wave associated with the shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Moreover, in experimental regimes where nonlinear viscous effects are dominant, reasonable comparisons with computed drag coefficients have been obtained; see e.g. [38].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, in experimental regimes where nonlinear viscous effects are dominant, reasonable comparisons with computed drag coefficients have been obtained; see e.g. [38].…”
Section: Introductionmentioning
confidence: 89%
“…[34]), and to account for possible slip, but also elastic and thixotropic effects can be present in certain regimes, see e.g. [37][38][39][40][41][42]. For example, in [39] detailed PIV studies of the velocity fields around spherical particles at extremely low speeds revealed significant asymmetry, which would not be present in any generalised Newtonian visco-plastic model.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The response of the fluid in this regime is less understood, but we assume that it is dominated by both shear banding and a competition between breakage and rejuvenation of the material. 18,19 A hysteresis is evident in regions ͑1͒ and ͑2͒. ͑3͒ Above these limits, i.e., in region ͑3͒, the data are consistent with a Herschel-Bulkley model and the three parameters were estimated through regression ͑see Table I͒.…”
Section: -3mentioning
confidence: 98%
“…12 and 10. In a related paper, 19 the appearance of shear waves generated by the settling sphere is observed and the development of shocks and a Mach cone under supercritical conditions is studied in detail. Recently there has been renewed interest in this problem due to the availability of ͑digital͒ particle image analysis ͑PIV͒.…”
Section: Introductionmentioning
confidence: 99%